Strategie radzenia sobie z bólem pacjentów z przewlekłą chorobą internistyczną = Strategies of coping with pain in patients with chronic internal disease - Bożena Baczewska; Beata Kropornicka; Katarzyna Dobrzyńska; Bogusław Block; Ewa Krzyżanowska; Robert Łuczyk; Cecylia Olszak; Elżbieta Nowicka; Regina Lorencowicz; Bożena Muraczyńska (Kazimierz Wielki University, 2017)
Baczewska Bożena, Kropornicka Beata, Dobrzyńska Katarzyna, Block Bogusław, Krzyżanowska Ewa, Łuczyk Robert, Olszak Cecylia,Nowicka Elżbieta, Lorencowicz Regina, Muraczyńska Bożena. Strategie radzenia sobie z bólem pacjentów z przewlekłą chorobą internistyczną = Strategies of coping with pain in patients with chronic internal disease. Journal of Education, Health and Sport. 2016;6(11):281-298. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.167127 http://ojs.ukw.edu.pl/index.php/johs/article/view/3994       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.11.2016. Revised 12.11.2016. Accepted: 16.11.2016.       Strategie radzenia sobie z bólem pacjentów z przewlekłą chorobą internistyczną Strategies of coping with pain in patients with chronic internal disease   Bożena Baczewska1, Beata Kropornicka1, Katarzyna Dobrzyńska1, Bogusław Block2, Ewa Krzyżanowska1, Robert Łuczyk1, Cecylia Olszak1, Elżbieta Nowicka1, Regina Lorencowicz3, Bożena Muraczyńska4   1 Katedra Interny z Zakładem Pielęgniarstwa Internistycznego Wydział Nauk o Zdrowiu Uniwersytetu Medycznego w Lublinie 2 Katedra Psychoterapii i Psychologii Zdrowia Katolicki Uniwersytet Lubelski im. Jana Pawła II. OTS Lublin 3 Katedra i Zakład Pielęgniarstwa Neurologicznego Wydział Nauk o Zdrowiu Uniwersytetu Medycznego w Lublinie 4 Katedra Chirurgii i Pielęgniarstwa Chirurgicznego Wydział Nauk o Zdrowiu Uniwersytetu Medycznego w Lublinie     Streszczenie Wstęp. Ból jest cennym objawem diagnostycznym, jednak w chwili kiedy przybiera charakter przewlekły wpływa negatywnie na każdy aspekt życie człowieka, zarówno biologiczny, psychiczny, jak również nie pozwala na pełnienie dotychczasowych ról społecznych. Ból w chorobach internistycznych jest najczęściej wskaźnikiem zaostrzenia choroby i zmusza do podejmowania działań, których celem jest jego łagodzenie. Działania te określa się jako strategie radzenia sobie z bólem. Celem badań było określenie strategii radzenia sobie z bólem pacjentów z przewlekłą chorobą internistyczną. Materiał i metoda. Badaniami objęto 200 pacjentów chorujących na przewlekłe choroby internistyczne, leczonych w Klinice Gastroenterologii z Pracownią Endoskopową oraz pacjentów Poradni Gastroenterologicznej oraz Reumatologicznej Przyklinicznej Przychodni Specjalistycznej Samodzielnego Szpitala Klinicznego Nr 4 w Lublinie. W badaniach posłużono się standaryzowanymi narzędziami badawczymi. W celach badawczych wykorzystano Kwestionariusz Strategii Radzenia Sobie z Bólem (CSQ), Skala wizualno - analogowa VAS oraz Kwestionariusz Autorski.  Wyniki badań. W badanej grupie wystąpiły wszystkie strategie radzenia sobie z bólem, do najczęściej stosowanych strategii należały modlenie się, zwiększona aktywność behawioralna jak również deklarowanie radzenia sobie. W wyniku przeprowadzonych badań stwierdzono istotny związek między nasileniem dolegliwości bólowych, wykształceniem, aktywnością zawodową badanych a wyborem prezentowanej strategii. Wnioski. U osób nieaktywnych zawodowo, jak również z niższym wykształceniem istotnie częściej występowały strategie radzenia sobie z bólem uznawane za przejaw nieefektywnego radzenie sobie z bólem niż u pozostałej grupy badanej.   Słowa kluczowe: strategie radzenia sobie w chorobie, ból, choroby internistyczne   Abstract Backgroud. Pain is a valuable diagnostic symptom, however long lasting pain has negative impact on an individual's  life, affecting biological, psychic and social functioning. In case of internal diseases pain of ten indicates exacerbation of illness, which additionally negatively affects the patient. Moreover, pain makes the patient under take activities to reduce its severity, which is referred to as coping strategies. The purpose of study was to examine strategies of coping with pain in the group of patients with chronic internal diseases. Material and methods. The study was conducted in the group of 200 patients suffering from chronic internal is eases treated in the Clinic of Gastroenterology with Endoscopy Unit and the patients treated in the Out-patient Clinics of Gastroenterology and Rheumatology, Hospital Out-patient Specialist Clinic , PSK-4, Lublin. The patients were surveyed by standardized questionnaires: Coping Strategies Questionnaire (QSC), Visual Anolog Scale VAS and a question naire developed by the author for the purpose of research. Results. The results revealed all strategies of coping with pain, the most frequent among them were prayers, increased behavioral activity, and self- declaration of coping. In addition, they found significant correlation between increased pains, education, professional activity and choice of coping strategy. Conclusions. Patients who were not active professionally, and the persons with lower level of education used coping strategies considered as ineffective statistically significantly more often compared to other examined groups.   Key words: strategies for coping with illness, pain, disease internist